2017
DOI: 10.1007/s00424-017-2037-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of temperature on FAD and NADH-derived signals and neurometabolic coupling in the mouse auditory and motor cortex

Abstract: Tight coupling of neuronal metabolism to synaptic activity is critical to ensure that the supply of metabolic substrates meets the demands of neuronal signaling. Given the impact of temperature on metabolism, and the wide fluctuations of brain temperature observed during clinical hypothermia, we examined the effect of temperature on neurometabolic coupling. Intrinsic fluorescence signals of the oxidized form of flavin adenine dinucleotide (FAD) and the reduced form of nicotinamide adenine dinucleotide (NADH), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1
1

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 107 publications
0
13
0
Order By: Relevance
“…To examine the circuit mechanisms underlying the stochasticity of the responses, brain slices that retained connectivity between the IC, MGB, TRN and AC were used. The aCTC mouse brain slice ( 3133 ), had an advantage that it retains the synaptic connections between these structures: hence, electrical stimulation of the IC was able to evoke a neuronal activity in all of these brain structures indicated by stimulus-evoked FA and Ca-signals as shown in Figure 2A and B. Both images showed only the average of the stimulus-evoked activity of the connected brain structures in the aCTC slice after several trials of IC stimulation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To examine the circuit mechanisms underlying the stochasticity of the responses, brain slices that retained connectivity between the IC, MGB, TRN and AC were used. The aCTC mouse brain slice ( 3133 ), had an advantage that it retains the synaptic connections between these structures: hence, electrical stimulation of the IC was able to evoke a neuronal activity in all of these brain structures indicated by stimulus-evoked FA and Ca-signals as shown in Figure 2A and B. Both images showed only the average of the stimulus-evoked activity of the connected brain structures in the aCTC slice after several trials of IC stimulation.…”
Section: Resultsmentioning
confidence: 99%
“…For all in-vitro experiments, 15-18 days old mice were initially anesthetized with ketamine (100 mg/ kg) and xylazine (3 mg/kg) intraperitoneally and transcardially perfused with chilled (4 °C) sucrose-based slicing solution containing the following (in mM): 234 sucrose, 11 glucose, 26 NaHCO 3 , 2.5 KCl, 1.25 NaH 2 PO 4 , 10 MgCl 2 , 0.5 CaCl 2 . After the brain was taken out, it was cut to obtain auditory colliculo-thalamocortical brain slice (aCTC) as shown (Figure S1) and as described before ( 3133 ). 600 μm thick horizontal brain slices were obtained to retain the connectivity between inferior colliculus (IC), medial geniculate body (MGB), thalamic reticular nucleus (TRN) and AC.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We routinely observe these spontaneous activations in all brain slices that contain the cerebral cortex and are bathed in concentrations of SR95531 above 0.5 μM and generally such activations occur roughly every 30-60 seconds with no obvious periodicity. These electrical events strongly resemble the intra- and extracellular manifestations of paroxysmal depolarizing shifts, respectively [8992], and we have previously found that they correlate with paroxysmal depolarizing shifts [93]. Therefore, we refer to them as paroxysmal depolarizations.…”
Section: Methodsmentioning
confidence: 84%
“…To obtain these data, a two month-old male mouse expressing GCaMP6s on a Thy1 promoter (Jackson labs, Stock No: 024275) was used. 400 µm thick coronal brain slices through the motor cortex, as previously described (Ibrahim, 2017). Brain slices were exposed to a low concentration of a bath-applied GABAA blocker (GABAzine, 100 nM) to induce spiking activity.…”
Section: Research Goalsmentioning
confidence: 99%